Fuel penalty from periodic rich combustion of a diesel fuelled engine during lean NOx trap purging - Alimin, Ahmad Jais (2007)
Compression ignition engines produce excessive NOX emissions compare to spark ignition engines. Lean NOX trap system is currently being investigated as an aftertreatment device to suppress the NOX emissions from compression ignition engines. The application of this aftertreatment device requires alternating lean and rich exhaust gas mixture, in order to produce the necessary reducing agents necessary for purging the LNT system. In this study an engine testbed was set-up which consisted of a 4-cylinder light-duty diesel engine, a diesel oxidation catalyst (DOC) and an LNT system. The LNT system purging utilised in-cylinder enrichment method based on DSPACE system, which controlled the engine management system (EMS) and the main engine operating parameters. The enrichment method used open-loop control system, to provide different storage/purge cycles for the LNT system. During enrichment, extra fuelling was needed to produce the required rich exhaust mixture. Emissions test at low operating temperature using this method had shown the capability of this in-cylinder enrichment method to produce the required periodic rich exhaust mixture for the LNT system. Nevertheless, the occurrences of periodic rich combustion also led to the increase in fuel penalty. Therefore, an acceptable trade-off between emissions reduction and fuel penalty is necessary.